Комплексний підхід до автоматизації теплообмінників - Кроніковський, Д. О. (Видавництво Львівської політехніки, 2011)
Described traditional approaches of automation of heat exchangers and the necessity of improvement. We suggest technique of diagnosing problems with heat exchangers based on method of parametrical identification and Shuhart maps.
Keywords: heat exchanger; diagnostics